2002
DOI: 10.1103/physreva.66.052114
|View full text |Cite
|
Sign up to set email alerts
|

Einstein-Podolsky-Rosen correlations of spin measurements in two moving inertial frames

Abstract: The formula for the correlation function of spin measurements of two particles in two moving inertial frames is derived within Lorentz-covariant quantum mechanics formulated in the absolute synchronization framework. These results are the first exact Einstein-Podolsky-Rosen correlation functions obtained for Lorentz-covariant quantum-mechanical systems in moving frames under physically acceptable conditions, i.e., taking into account the localization of the particles during the detection and using the spin ope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 38 publications
2
52
2
Order By: Relevance
“…We realize that the point remains concerning the lack of the manifest covariance of the theory which is usually pointed out as the second main disadvantage of the Salpeter equation. However, it is our belief that this flaw can be circumvented by using the preferred frame approach which has been already successfully applied for the Lorentz covariant localization in quantum mechanics [38], relativistic EPR correlations [39], and Lorentz covariant formulation of classical and quantum statistical mechanics [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…We realize that the point remains concerning the lack of the manifest covariance of the theory which is usually pointed out as the second main disadvantage of the Salpeter equation. However, it is our belief that this flaw can be circumvented by using the preferred frame approach which has been already successfully applied for the Lorentz covariant localization in quantum mechanics [38], relativistic EPR correlations [39], and Lorentz covariant formulation of classical and quantum statistical mechanics [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 More recently the some general behavior of the entangled behavior of quantum states has been studied in the literature. The first steps were taken in the context of special relativity [16][17][18][19][20][21] and later they were integrated within the framework of general relativity for the Schwarzschild spacetime 22 and for the Kerr-Newman spacetime. 23 In particular for the case of the Schwarzschild spacetime, Terashima and Ueda 22 considered a pair of spinning particles in an entangled state moving on equatorial motion.…”
Section: Introductionmentioning
confidence: 99%
“…As has been recognized, this presupposes a tremendous 'speed of information' [82] and a preferred inertial frame [80]. Nevertheless, it can be shown that assumptions of completeness and probablistic nature of measurements suffice to ensure that any model of quantum mechanics does not violate no-signalling and Lorentz-covariance at the level of measurement outcomes even if the speed of information is superluminal [84].…”
Section: 5×10mentioning
confidence: 99%